Length Measurement of Long Gauge Blocks by Interferometer - Kanokporn Kohmun; Pichet Limsuwan; Monludee Ranusawud; Prathan Buranasiri (My University, 2020)
A gauge block interferometer with a vacuum chamber was designed and constructed for the measurement of gauge block lengths between 10 to 1,000 mm. In the chamber, four gauge blocks under the length measurement can be mounted on the measuring table. Furthermore, the length of all four gauge blocks can be measured continuously in one measurement. In this study, four gauge blocks with the nominal length of 125, 200, 400 and 500 mm were used for the length measurement. The environment parameters in the vacuum chamber including temperature, pressure, relative humidity and CO2 concentration were measured. The refractive index of air which depends on environment parameters was determined by using updated Edlén equation. Then, the lengths of four gauge blocks were measured and found to be 125.00025, 200.00019, 400.00070 and 500.00064, respectively.
Keywords: Length measurement; Pressure measurement; Advanced Measurement and Metrology Techniques